PENGGUNAAN MODEL RESOURCE BASED LEARNING (RBL) DALAM PENINGKATAN PEMBELAJARAN IPA PADA SISWA KELAS IV SD NEGERI 2 KARANGSARI TAHUN AJARAN 2013/2014 - Noviana, Lutfi Tri (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: . The Use Of Resource Based Learning (RBL) Model In Improving Natural Science Learning At 4th Grade Student Of SD Negeri 2 Karangsari Academic Year 2013/2014. The purpose of this research is to improve the natural science learning of elementary school 4th grade student with the use of resource based learning model. The research was conducted in three cycles. Every cycles is consist of planning, action, observation, and reflection. The results of this study can improve the process and learning outcome. The subject of this research were 4th grade elementary school students. Data sources of this study are students, teachers, observers, and documents. Data was collected with tests and non-test techniques. The validity of the data using triangulation  of sources andt riangulation techniques. Conclusion of research is the use of resource based learning model can improving natural science learning in 4th grade elementary school students Of SD Negeri 2 Karangsari academic year 2013/2014. Keywords: resource based learning model, improved learning, natural science Abstrak: Penggunaan Model Resource Based Learning (RBL) Dalam Peningkatan Pembelajaran IPA Pada Siswa Kelas IV SD Negeri 2 Karangasari Tahun Ajaran 2013/2014. Tujuan penelitian ini adalah untuk meningkatkan pembelajaran IPA pada siswa kelas IV SD dengan penggunaan model resource based learning. Penelitian ini dilaksanakan dalam tiga siklus. Setiap siklus terdiri dari tahap perencanaan, pelaksanaan, observasi, dan refleksi. Hasil penelitian ini yaitu dapat meningkatkan proses dan hasil belajar. Subjek penelitian ini adalah siswa kelas IV SD. Sumber data penelitian ini adalah siswa, guru, observer dan dokumen. Teknik pengumpulan data dilakukan dengan teknik tes dan non tes. Validitas data menggunakan triangulasi sumber dan triangulasi teknik. Simpulan penelitian ini adalah penggunaan model pembelajaran resource based learning dapat meningkatkan pembelajaran IPA pada siswa kelas IV SD Negeri 2 Karangsari tahun ajaran 2013/2014 Kata kunci: Model Resource Based Learning, Peningkatan pembelajaran, IPA